Some Economic Implications of Unemployment Insurance - Yoder, Dale (Quarterly Journal of Economics, 1931)
I. Recent proposals for unemployment insurance require special consideration, 622.—II. Systems established voluntarily by employers are practical only under certain conditions, 624.—III. Profits and surpluses not a suitable source of unemployment insurance funds, 626.—Nor employers' gains resulting from the lag of money wages, 629.—Doubtful whether unemployment insurance will pay for itself through increased productivity, 630.—IV. Compulsory contributions to unemployment funds tend to fall upon wage-earners, 633; and not likely to lead to reduction of unemployment, 634.—V. Direct government subsidies the proper method, 639.